Virtual simulation technology based research on subsoiling process. (March 2019) - Lin, Yulong; Yang, Li; Liu, Shourong; Zhao, Xueyan; Cao, Chao; Li, Chunlin
A novel simulation method to research subsoiling process is proposed in this paper. The influence of changing depth of tines cutting soil caused by subsoiler's structure, road roughness and excitation of tyre and road on subsoiling is investigated. Soil model is divided into three layers, the different characteristics of soil in different depths are also considered. Firstly, a 3D geometry model of tractor–subsoiler system is established. Secondly, road roughness test is designed to measure elevation data of a farmland, then its surface is reconstructed based on harmonic superposition theory. Thirdly, a virtual prototyping model of tractor–subsoiler system is developed, and the depth curves of tines cutting soil with time are obtained based on the reconstructed farmland. Finally, with the method of finite element method (FEM) and smoothed particle hydrodynamics (SPH) coupling, MAT147 (MAT_FHWA_SOIL) soil material model which is layered, and depth curves of tines cutting soil, the finite element dynamic analysis of tines cutting soil is simulated. With subsoiling resistance as verification index, the simulation data are compared with the field experimental data. Under subsoiler oscillatory operation, the error rate of simulation is 3.78%. Under subsoiler non-oscillatory operation, the error rate of simulation is 5.02%. The simulation results agree well with the experimental results, which proves that the proposed simulation method can be a good substitute for the subsoiling physical test.